A Rijeka-Koper dichotómia sajátosságai a magyar agrárexportot illetően a Rail Cargo Hungária Zrt. tevékenysége példáján - Bali, Lóránt (Közép-Európai Közlemények, 2015)
Current political events have a significant impact on the development of transport infrastructure in addition to political geographical factors. Over the last 25 years, Western-Balkans lived through one of the greatest European geopolitical realignment. Regarding to my topic I cannot ignore the changes took place in the years of socialism before the regime change which basically determined the later situation of Rijeka (Fiume) and Koper. In my study I will demonstrate the relationship of Adriatic Sea ports with special focus on Hungarian transport. Previously I examined the status of Rijeka in the socialism and the maritime trade development policy of Yugoslavia.